A report of adenocarcinoma in situ and congenital pulmonary airway malformation in a three-day-old infant with a review of the literature - Balkanlı, Süleyman; Özturk, Mehmet Adnan; Köse, Mehmet; Baştuğ, Osman; Tekelioğlu, Fatoş; Hasdıraz, Leyla; Doğanay, Selim (The Turkish Journal of Pediatrics, 2014)
Association between malignancy and congenital pulmonary airway malformation is a rare entity in childhood. Herein, we describe a three-day-old infant with respiratory distress and cystic lung lesion on her left lung. A lobectomy was performed at the age of three days, and the patient was diagnosed with congenital pulmonary airway malformation and adenocarcinoma in situ.